Venous Leg Compression for Tissue Decongestion in Patients With Worsening Congestive Heart Failure - Civera, Jose; Miñana, Gema; de la Espriella, Rafael; Santas, Enrique; Sastre, Clara; Mollar, Anna; Conesa, Adriana; Martínez, Ana; Núñez, Eduardo; Bayés-Genís, Antoni; Núñez, Julio (Frontiers in Cardiovascular Medicine, 2022)
Aims. Venous leg compression (VLC) with elastic bandages has been proposed as a potentially useful strategy for decreasing tissue congestion. We aimed to evaluate the effect of VLC on short-term changes on intravascular refill, assessed by inferior vena cava (IVC) diameter in patients with worsening heart failure (WHF) requiring parenteral furosemide. Additionally, we sought to evaluate whether early changes in IVC were related to short-term decongestion. Methods. This is a prospective study in which we included 20 consecutive ambulatory patients with WHF treated with subcutaneous furosemide and VLC for at least 72 hours. The endpoints were a) short-term changes in IVC, b) the association between decongestion and 3-hour IVC changes following VLC. Changes in continuous endpoints and their longitudinal trajectories were estimated with linear mixed regression models. All analyses were adjusted for multiple comparisons. Results. Following administration of subcutaneous furosemide and VLC, we found a significant increase in 3-hour IVC diameter (ΔIVC=1.6 mm, CI 95%: 0.7-2.5; p<0.001), with a greater increase in those with baseline IVC≤21 mm (2.4 mm vs. 0.8 mm; p<0.001). 3-hour intravascular refill (increase in IVC≥2 mm) was associated with greater decongestion (natriuresis, weight, peripheral edemas, and dyspnea) in those with baseline IVC≤21 mm but not when IVC>21mm (p<0.05 for all comparisons). Conclusions. In this cohort of patients with congestive WHF treated with subcutaneous furosemide and VLC, we found a greater increase in short-term IVC in those with IVC ≤21 mm at baseline. In this subset of patients, a 3-hour increase in IVC≥2 mm was associated with greater short-term decongestion.